A Pilot Randomized Trial of an Intervention to Enhance the Health-Promoting Effects of Older Adults' Activity Portfolios: The Engaged4Life Program. Issue 8 (17th November 2018) - Matz-Costa, Christina; Lubben, James; Lachman, Margie E.; Lee, Haenim; Choi, Yeon Jin
ABSTRACT: The purpose of this study was to evaluate the feasibility and outcomes of the Engaged4Life program, an intervention to encourage inactive community-dwelling older adults to embed physical activity, cognitive activity, and social interaction into their everyday lives in contexts that are personally meaningful and natural for them. Fifteen participants were randomized to the intervention group (technology-assisted self-monitoring of daily activity via pedometers and daily tablet-based surveys; psychoeducation + goal-setting via a 3-hour workshop; and peer mentoring via phone 2×/week for 2.5 weeks) and 15 to the control (technology-assisted self-monitoring only). Recruitment was shown to be feasible and efficient, but not able to reach the target for men. Retention rate was 83% and participants manifested high adherence and engagement with the intervention. Though this pilot trial was not powered to demonstrate significant differences between groups, daily steps increased by 431 (11% increase) from baseline to Week 4 for the intervention ( p < .05), but decreased by 458 for the control, for a net difference of 889 steps ( p < .05). Findings were sustained at Week 8 ( p < .01). In a future trial, difficulties in recruiting men, barriers due to the technology-intensive design, and the optimization of secondary outcome measures should be addressed.